Enhancing the Photovoltaic Performance of Ladder‐Type Heteroheptacene‐based Nonfullerene Acceptors by Incorporating Halogen Atoms on Their Ending Groups. (19th February 2021) - Wan, Shuo; Ma, Yunlong; Cai, Dongdong; Lin, Wenyuan; Wang, Pengsong; Wang, Jinyun; Zheng, Qingdong
Abstract: Ending group halogenation is an effective strategy for modulating the energy levels, bandgaps, and intermolecular interactions of nonfullerene acceptors. Understanding the influence of different halogen atoms on the acceptor properties is of great importance for designing high‐performance nonfullerene acceptors. Here, three acceptor–donor–acceptor (A‐D‐A) type nonfullerene acceptors (M5, M6, and M7), which are constructed by using a ladder‐type heteroheptacene core without the traditional sp 3 carbon‐bonded side chains as the electron‐rich core, and 2‐(3‐oxo‐2, 3‐dihydro‐1H‐inden‐1‐ylidene)malononitrile without or with halogen atoms as the ending groups. The nonfullerene acceptors with chlorinated (M6) and brominated (M7) ending groups exhibit broadened absorption spectra, down‐shifted energy levels, and enhanced molecular ordering compared to the counterpart without any halogenated ending groups (M5). Among the nonfullerene acceptors, M6 has the strongest intermolecular ππ interaction with its shortest ππ interaction distance and the longest coherent length which are beneficial for enhancing the charge transport and therefore boosting the photovoltaic performance. An excellent power conversion efficiency of 15.45% is achieved for the best‐performing polymer solar cell based on M6. These results suggest that the halogenated ending groups are essential for high‐performance heteroheptacene‐based nonfullerene acceptors considering their simultaneous enhancements in both the light‐harvesting and the charge transport. Abstract : Three nonfullerene acceptors (M5, M6, and M7) are developed by using different ending groups, among which M6 with chlorinated ending groups exhibits a reduced ππ interaction distance with enhanced molecular ordering compared to M7 (or M5) with brominated (or unsubstituted) ending groups. With a wide‐bandgap copolymer, the best‐performance device based on M6 exhibits an outstanding power conversion efficiency of 15.45%.